2019
DOI: 10.1111/sdi.12784
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and physical activity for people receiving peritoneal dialysis: Why not?

Abstract: People with end‐stage kidney disease (ESKD) receiving peritoneal dialysis (PD) are physically inactive leading to low physical function and poor health outcomes. Guidelines recommend that nephrologists encourage PD patients to increase their activity levels; however, PD patients are often discouraged from participating in exercise programs because of perceived barriers and a lack of precision about the appropriate exercise regimen. This review suggests ways forward to assist nephrology professionals to encoura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 27 publications
1
42
0
2
Order By: Relevance
“…The two specific PD questions revealed that the vast majority of patients did not feel their catheter or fluid in their peritoneum affected their ability to exercise. The finding that in the minds of the patients the PD catheter and PD fluid are not a barrier to activity is highly encouraging, as these have been previously reported as potential barriers to exercise (Isnard‐Rouchon et al 2019). The finding may also be a result of all respondents receiving APD, which reflected our service where 94% of patients receive APD and only 6% receive continuous ambulatory PD.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The two specific PD questions revealed that the vast majority of patients did not feel their catheter or fluid in their peritoneum affected their ability to exercise. The finding that in the minds of the patients the PD catheter and PD fluid are not a barrier to activity is highly encouraging, as these have been previously reported as potential barriers to exercise (Isnard‐Rouchon et al 2019). The finding may also be a result of all respondents receiving APD, which reflected our service where 94% of patients receive APD and only 6% receive continuous ambulatory PD.…”
Section: Discussionmentioning
confidence: 76%
“…Given the positive perceptions towards exercise the questions arises “What are peritoneal dialysis providers doing to promote physical activity and exercise?” Given the lack of knowledge and evidence regarding what exercise is right for PD patients, the involvement of exercise professionals may be the answer (Isnard‐Rouchon et al 2019; Uchiyama et al 2019). Exercise professionals such as exercise physiologists, physical therapists, kinesiologists and athletic trainers, can provide exercise assessments, programmes and goal setting agreements with patients.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of exercise programs for PD patients have been reported in China, 18 , 19 France, 12 and Japan, 20 with no sustained exercise programs in the United States being reported in the past 20 years. 21 Exercise in PD research studies are also scarce, consisting mainly of smaller studies and heterogeneous outcomes 21 , 22 with no large interventional PD exercise (PDEx) studies reported in the United States.…”
mentioning
confidence: 99%
“…Although some studies report that increased physical activity (PA) levels in patients with PD can generate benefits in controlling increased cardiovascular morbidity, mortality and loss of function, the effects of PA in patients on PD remain doubtful [9]. Recently practitioners have suggested that PD patients should increase their PA levels, as this increase allows patients to improve their quality of life and to reduce the adverse effects of inactivity [10].…”
Section: Introductionmentioning
confidence: 99%